Lung Dysfunction and Mortality in Patients with Chronic Kidney Disease - Hideyuki Mukai; Pei Ming; Bengt Lindholm; Olof Heimbürger; Peter Barany; Peter Stenvinkel; Abdul Rashid Qureshi (Karger Publishers, 2018)
Background/Aims: Lung dysfunction associates with increased mortality but the impact of chronic kidney disease (CKD) is less clear. We evaluated lung function and its association with mortality among individuals with normal to severely reduced glomerular filtration rate (GFR). Methods: 404 individuals representing GFR category G1 (n=31; GFR >90 mL/min/1.73 m2), G2 (n=46), G3 (n=33), G4 (n=49) and G5 (n=245; GFR< 15 mL/min/1.73 m2) underwent spirometry yielding lung function indices forced vital capacity (FVC), forced expiratory volume in the first second (FEV1) and peak expiratory flow (PEF). Associations of lung function indices expressed as percentages of predicted values (%FEV1, %FVC and %PEF) with 5-year mortality were analyzed by competing-risk regression models. Results: The prevalence of obstructive (6% in G1 and 11% in G5) and especially restrictive (9% in G1 to 36% in G5) lung dysfunction increased with declining GFR and with higher comorbidity burden. In patients (n=22) with protein-energy wasting, inflammation and cardiovascular disease, the prevalence of restrictive lung function was 64%. The highest tertiles of % FEV1 and %FVC associated with lower sub-hazard ratios (sHR) for all-cause mortality, 0.49 (95% CI, 0.27-0.88)) and 0.56 (95% CI, 0.32-0.98), and that of %FEV1 also with lower cardiovascular mortality risk (sHR 0.16; 95%CI 0.04-0.69) after adjusting for multiple confounders. Restrictive lung dysfunction (FEV1/FVC ≥ 0.70, and %FVC < 80) associated with increased mortality risk (sHR 1.80, 95%CI, 1.04-3.13) while the association with obstructive lung impairment was not statistically significant. Conclusion: Lung dysfunction and in particular restrictive lung dysfunction associates with degree of renal function impairment and presence of comorbidities, and is an independent predictor of increased mortality in CKD patients.